The Trend of Drug Therapy on Uveitic Macular Edema: A Bibliometric Analysis of the 100 Most Cited Articles - Chen, Si; Kong, Jinfeng; Feng, Lei (Frontiers in Medicine, 2022)
Background: Macular edema is the most common cause of impaired vision due to uveitis. Although various medications are available, not all uveitis patients with macular edema are satisfied with the treatment results. Therefore, solving this gap becomes the utmost concern worldwide. This study attempted to use bibliometric analysis to compare the valuable information in the top 100 highly cited studies in the field of drug therapy for uveitic macular edema (UME) and then determine the research hot spots and trends in this field. Methods: In this study, the Science Citation Index Expanded (SCIE) of Web of Science (WOS) was used to collect the top 100 most cited studies on UME and analyze the literature from different countries/regions, institutions, and journals. The visualization knowledge maps is generated by VOSviewer and Citespace software. Results: The top 100 highly cited studies are from 34 countries/regions. The United States has the largest number of publications, followed by the England, Spain and Germany. The top three institutions publishing highly cited literature are all from the England: University of London, University College London, and Moorfields Eye Hospital NHS Foundation Trust. Ophthalmology is the most widely published journal with 14 papers. The total number of citations is 1371, meaning that Ophthalmology is the most authoritative journal in the field of UME drug therapy. The top two articles with the most cited times are from the United States, accounting for 36.5% of the total cited times of the top 10 articles. Keywords were divided into three clusters: the corticosteroid administration pathway, biological agents, and clinical trials. Uveitis, cystoid macular edema, efficacy, dexamethasone and triamcinolone acetonide appeared more frequently in keywords. Researches on local and long-acting drug has gradually becoming the hot spots and trends. Conclusion: This study concludes that bibliometric analysis can intuitively and quickly obtain the frontiers and hot spots of research in the field of UME drug therapy. Corticosteroid administration, biological agents, and clinical trials are considered the potential focus of future research.